Reflections on the theory of international trade : lectures given in the University of Manchester - Robinson, Joan (Manchester : Manchester University Press, 1974)
In these three lectures, delivered at Manchester University in 1973, the author considers the state of 'pure trade theory'; while aware of the real world significance of power and imperialism in trade, such considerations are left aside here
Includes bibliographical references.
osc 31/01/2019
Loans
Keywords: International trade; Commerce